Understanding and influencing agency and behavior change in Peru - Beltrán, Marcela; Tristán Febres, María Claudia; Freed, Sarah; Voss, Rachel C. (2023)
This country brief is part of the outputs for Work Package 5 (WP5) of the CGIAR Initiative on Agroecology. The focus of WP5 is understanding and then influencing individual and collective agency and behavior among food system actors (FSAs) to drive inclusive and equitable agroecological transformation. To achieve this, a good starting point is to learn from past agroecological experiences in the Agroecological Living Landscapes (ALL). This brief identifies trends in agroecological (AE) initiatives or other initiatives that make a significant contribution to food systems’ agroecological transformation and seeks to understand the initiatives’ approaches to behavior change as well as the behavior determinants/drivers that facilitated or impeded the agroecological innovations.